Microbial Fuel Cell Based Polystyrene Sulfonated Membrane as Proton Exchange Membrane - S Muljani; A Wulanawati (UNIVERSITAS SEBELAS MARET (UNS), 2016)
Microbial fuel cell (MFC) represents a major bioelectrochemical system that converts biomass spontaneously into electricity through the activity of microorganisms. The MFC consists of anode and cathode compartments. Microorganisms in MFC liberate electrons while the electron donor is consumed. The produced electron is transmitted to the anode surface, but the generated protons must pass through the proton exchange membrane (PEM) to reach the cathode compartment. PEM, as a key factor, affects electricity generation in MFCs. The study attempted to investigate if the sulfonated polystyrene (SPS) membrane can be used as a PEM in the application on MFC. SPS membrane has been characterized using Fourier transform infrared spectrophotometer (FTIR), scanning electron microscope (SEM) and conductivity. The result of the conductivity (σ) revealed that the membrane has a promising application for MFC.